Social Media as Digital Marketing Tool in MSME: A Systematic Literature Review - Agustina, Aninda; Ambarwati, Rita; Sari, Herlinda Maya Kumala (Universitas Proklamasi 45, 2023)
The pandemic has caused difficulties for micro, small, and medium enterprises (MSMEs) in managing their finances, as all activities have been temporarily halted for health recovery. As a result, MSMEs have experienced losses in sales. One of the ways to ensure continuous sales and attract more buyers is by utilizing digital marketing. There are various options available in digital marketing, and one of them is leveraging social media platforms. MSME players have started to venture into digital marketing to increase their sales volume. However, previous research has shown that it has been only partially effective despite utilizing social media for sales facilitation. To address this issue, a Systematic Literature Review was conducted to document and review all articles related to enhancing social media utilization as a digital marketing tool to facilitate sales for MSMEs. A total of 20 nationally and internationally accredited journal articles were accessed from DOAJ, Google Scholar, and lens.org. The findings of the literature review study analyzed these 20 research articles that suspected social media as a digital marketing strategy to facilitate sales for MSMEs.